Communities in the time of crisis - Ρηγοπούλου Καλλιόπη (The Greek Review of Social Research, 2011)
In the present situation of global crisis the discourse concerning communities acquires a new importance. This discourse regards two different yet intermingling fields, both in Greece and in many other countries: on the one hand it concerns concrete historical phenomena and on the other aesthetic and ideological discussions leading to the invention and materialization of vanguard social and artistic experiments using references to the past in order to produce answers for the present. The present article analyses the situation in which this discussion takes place in the present day, when the common (koinon) element is particularly difficult to grasp and proceeds to a solution drawing inspiration from Cervantes’s Don Quichotte. This consists of a kind of «creative regression» leading to the encounter with exemplary personalities and moments, like the Russian artistic colony of Abramchevo and the experiment of Eva and Angelos Sikelianos in Delphi. Discussing such cases can become useful in order to conceive new models of creation, organization and action.